그린리모델링 사례분석을 통한 요소기술 우선순위 도출 - 공공어린이집을 중심으로 - 방주예(Jooye Bang); 임세현(Sehyeon Lim); 심성진(Sungjin Sim); 김성은(Seongeun Kim); 송용우(Yongwoo Song); 박진철(Jinchul Park) (KIEAE Journal, 2024)
Purpose: In order to cope with the climate crisis caused by global warming, greenhouse gas reduction goals are being proposed worldwide. The Korean government is setting goals for reducing greenhouse gas emissions by sector through the 2030 National Greenhouse Gas Reduction Basic Roadmap. Among them, the construction sector has set a goal of reducing greenhouse gas emissions by about 32.8% by 2030. To achieve this, zero-energy buildings for new buildings and green remodeling projects for existing buildings are being promoted. Currently, in Korea, the proportion of old buildings is expected to increase by about 21.9% after the next 10 years. Considering that the importance of green remodeling is attracting more attention as the proportion of old buildings gradually increases, this study intends to derive priorities for each elemental technology targeting daycare centers for efficient green remodeling. Method: The data before and after green remodeling were checked for 69 daycare centers that have been green remodeled. In order to build the base-model, the average value of all daycare centers was derived, and the base-model was compared by green remodeling element technology. Result: As a result of comparing the primary energy consumption reduction rate by green remodeling element technology, the total heat exchanger saved the most at 15.57%, followed by high performance windows and doors, and high efficiency air conditioners. By deriving these priorities, efficient green remodeling can be performed. KCI Citation Count: 0